Analysis of Brand Reputation toward Purchase Intention among Muslimah Fashion Customers on Instagram : A Case of Amberlyn Indonesia - Al Ikhsani, Mayang; Putro, Utomo Sarjono (Journal of Innovation, Business and Entrepreneurship, 2019)
Instagram as a muslim fashion entrepreneur platform to introduce, sell and promote a variety of products. Indonesia is a country with the majority of its population is Islam and the need for muslimah fashion is quite high, fashion is important for someone to meet their needs and pay attention to appearance. Amberlyn Indonesia is one of the muslimah fashion industry in Indonesia that makes Instagram a major online market in introducing, selling, and promoting various product variations. Amberlyn found the fact that the reputation factor was classified as poor from various competitors. From this problem Amberlyn's CEO conducted a study related to the level of influence of reputation on buying interest in muslimah fashion customers on Instagram. From this study found the fact that reputation strongly influences purchase intention in the amount of 0.495. Then for each addition of 1 unit reputation value, the purchase intention value from customers will increase by 85%. Based on this fact Amberlyn Indonesia's CEO made the decision to develop Amberlyn in the aspect of reputation, namely trust, product quality, and product innovation to increase customer’s purchase intention. Keywords : Reputation, purchase intention, muslimah fashion, Instagram.